2008
DOI: 10.1002/ejlt.200700259
|View full text |Cite
|
Sign up to set email alerts
|

Borage and evening primrose oil

Abstract: The paper gives a short overview about the production and composition of borage (Borago officinalis) and evening primrose (Oenothera biennis) oil considering special aspects of the production as cold‐pressed oil. Both oils are characterized by a remarkable amount of γ‐linolenic acid, which has some nutritional advantages. The fatty acid composition of evening primrose oil is dominated by linoleic acid with about 72% and about 13% γ‐linolenic acid, while borage oil consists of twice the amount of γ‐linolenic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
(28 reference statements)
3
30
0
Order By: Relevance
“…Borage seeds oil of the present study contained high percentage concentrations of linoleic (34.23%) and -linolenic (24.79%) acids. These fatty acids profile and concentrations are near to that reported in previous studies by Eskin (2008) and Tasset-Cuevas et al (2013). Total unsaturated fatty acids (83.31%) were higher than total unsaturated fatty acids (57.67%) observed by El-Gengaihi et al (2004) but similar to that observed by Khan and Shahidi (2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Borage seeds oil of the present study contained high percentage concentrations of linoleic (34.23%) and -linolenic (24.79%) acids. These fatty acids profile and concentrations are near to that reported in previous studies by Eskin (2008) and Tasset-Cuevas et al (2013). Total unsaturated fatty acids (83.31%) were higher than total unsaturated fatty acids (57.67%) observed by El-Gengaihi et al (2004) but similar to that observed by Khan and Shahidi (2000).…”
Section: Discussionsupporting
confidence: 89%
“…Borage oil hepatoprotection is connected with its antioxidant properties (Lukivskaya et al, 2012). The phytochemical constituents, tocopherols and GLA are responsible for this hepatoprotective effect of borage seeds oil (Eskin, 2008;Soto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interactions between amylose and fatty acids minimize the affinity of amylose for water molecules and reduce the hydrophilicity of the films [26]. BO contains various fatty acids including saturated fatty acids with different hydrocarbon chain lengths (palmitic, stearic, and arachidic acids) and USFAs (palmitoleic, oleic, linoleic, α-linolenic, γ-linolenic, and eicosanoic acids) [15,29], which create a barrier against moisture permeation. Several studies have similarly reported that increasing the fatty acid concentration decreased the WVP [14,23].…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Algae oil can be an extremely rich source of all discussed tocopherols other than δtocopherol (Frankel et al, 2002). Black currant seed (65 mg/100 g oil), borage (66 mg/100 g oil), evening primrose (34 mg/100 g oil), and sesame (24-52 mg/100 g oil) are substantial sources of γ-tocopherols (Speek et al, 1985;Reina et al, 1999;Eskin, 2008). Brazil nuts, pecans, pistachios, and walnuts are notable for fairly high quantities of both β-and γ-tocopherol.…”
Section: Associated Health Benefitsmentioning
confidence: 99%